2018
DOI: 10.3390/s18020580
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the Zenith Tropospheric Delay Estimates in On-line Precise Point Positioning (PPP) Services and PPP Software Packages

Abstract: As Global Navigation Satellite System (GNSS) signals travel through the troposphere, a tropospheric delay occurs due to a change in the refractive index of the medium. The Precise Point Positioning (PPP) technique can achieve centimeter/millimeter positioning accuracy with only one GNSS receiver. The Zenith Tropospheric Delay (ZTD) is estimated alongside with the position unknowns in PPP. Estimated ZTD can be very useful for meteorological applications, an example is the estimation of water vapor content in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 24 publications
0
34
1
2
Order By: Relevance
“…11 it is evident that no clear relationship exists between the RMS and station latitudes. The results in this study however, do not match with those reported by others such as Lu et al (2016) and Astudillo et al (2018). Therefore, the study on the quality of ZTD estimation at different latitudes needs to be further confirmed with much denser GPS network in the future.…”
Section: Comparison Between Gogps and Apps Ztdcontrasting
confidence: 93%
See 1 more Smart Citation
“…11 it is evident that no clear relationship exists between the RMS and station latitudes. The results in this study however, do not match with those reported by others such as Lu et al (2016) and Astudillo et al (2018). Therefore, the study on the quality of ZTD estimation at different latitudes needs to be further confirmed with much denser GPS network in the future.…”
Section: Comparison Between Gogps and Apps Ztdcontrasting
confidence: 93%
“…There is an increasing use of PPP for processing the GNSS data using different software packages that have been developed (Astudillo et al, 2018). However, the main problem of using the PPP method is the long interval of about 20-30 min required for the solution convergence (Dousa and Vaclavovic, 2014;Wonnacott and Merry, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The PPP positioning technique is widely implemented in many software and online services. A previous study [19] found that most online software available for PPP obtained very close values for the estimation of the ZTD. Thus, we can expect consistent results using any software.…”
Section: Introductionmentioning
confidence: 90%
“…The VMF1 model derived hydrostatic delays are provided in the Global Geodetic Observing System (GGOS) website [22] and are based on meteorological data from Numerical Weather Models (NWMs). ZHD can also be derived using a static model that is based on the station height only [23]. Static models are more appropriate for tropical stations, where temperature variations are minimal.…”
Section: A Gps-derived Water Vapor Contentmentioning
confidence: 99%